Wurster type covalent organic framework material, preparation method and application of Wurster type covalent organic framework material in gold adsorption
By constructing Wurster-type covalent organic frame material, using its multi-stage pore structure and high selectivity, the problems of low gold recycling efficiency and high cost in the prior art are solved, and efficient and economical gold element adsorption and recycling effects are achieved.
Patent Information
- Application Number
- CN202510037245.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The prior art has problems such as high raw material cost, complex synthesis process, needing additional energy input, low recovery capacity and lack of selectivity in gold recycling, and it is impossible to effectively adsorb and recover gold elements.
Using Wurster type covalent organic frame material, the ratio of linear monomer and V-shaped monomer is adjusted through the three-component mixed ligand strategy to construct a new three-component covalent organic frame with a multi-stage pore structure, which is used to efficiently adsorb gold elements in acidic solutions.
The efficient adsorption and recovery of gold elements is achieved, with a gold recovery rate of more than 99.9%, and it shows excellent selectivity and high adsorption capacity in the mixed leaching liquid of circuit board and CPU. The raw materials of the material are low and the synthesis method is simple.
Smart Images

Figure CN119735771A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of Wurster type covalent organic framework materials, in particular to a Wurster type covalent organic framework material, a preparation method and its application in gold adsorption Background Art
[0002] As electronic devices are updated at an accelerated pace, efficient and environmentally friendly recycling of gold from these resources can not only reduce dependence on natural gold mines, but also reduce the pollution of the environment by electronic waste.
[0003] Adsorption, precipitation, solvent extraction and ion exchange techniques have been widely used to recover gold from the leachate of electronic waste. Among them, the adsorption method based on porous adsorbents has gradually become the mainstream technology for gold recovery due to its environmental protection, low cost and simple operation.
[0004] Covalent organic frameworks (COFs) are a new class of highly crystalline, porous organic polymers. Organic building blocks connected by strong covalent bonds make COFs tunable in porosity, skeleton structure and chemical stability, and are widely used in the field of adsorption of precious metals.
[0005] Although many studies have achieved certain results in improving the adsorption performance of COFs, the existing technology faces disadvantages such as expensive raw material costs, complex synthesis process, additional energy input, low recovery capacity, and lack of selectivity.
[0006] For example, CN202210907161.3 discloses a crown ether covalent organic framework material, preparation method and application of adsorption separation of palladium, which can specifically adsorb and separate palladium from an acidic aqueous phase containing 19 metal ions, and the single-stage adsorption rate of palladium ions can be as high as 94% or more, with high selectivity, simple operation and high separation efficiency, and is particularly suitable for separation and recovery of precious metal palladium in the nuclear industry. However, the material cannot achieve effective adsorption of gold.
[0007] Another example is the porous composite material, preparation method and application disclosed in CN202211390039.X, which relates to the technical field of environmental functional materials. By forming a metal polyphenol network structure (MPN) in the pores and surface of the covalent organic framework (COFs) material, and combining the well-characterized COFs and MPN materials, a layered porous composite material COFs@MPN is synthesized. The prepared composite material has a high specific surface area and porous structure, and provides surface support for COFs, effectively improves the mechanical strength of COFs, changes the three-dimensional pore structure of COFs, and improves its adsorption performance and stability of caffeine in practical applications. This material still cannot be used for the effective adsorption of gold in an environment with a large number of impurity ions.
[0008] Therefore, there is an urgent need to develop a cheap and efficient gold recovery agent. The information disclosed in the background technology section is only intended to increase the understanding of the overall background of the present invention, and should not be regarded as admitting or suggesting in any form that the information constitutes the prior art known to ordinary technicians in the field. Summary of the invention
[0009] The present application provides a Wurster-type covalent organic framework material, a preparation method and application thereof in gold adsorption, which can be used as a cheap and efficient gold (Au) recovery agent.
[0010] The present application provides a Wurster type covalent organic framework material, the structural formula of which is any of the following:
[0011]
[0012]
[0013]
[0014] Another aspect of the present application also provides a use of the Wurster type covalent organic framework material as claimed in claim 1 in gold adsorption, with a gold recovery rate of >99.9%.
[0015] Another aspect of the present application also provides a method for gold element adsorption recovery, comprising: adding the above-mentioned Wurster type covalent organic framework material to an acidic solution, shaking and mixing, filtering, and adsorbing the gold element into the obtained solid;
[0016] The acid solution is an acid simulation solution containing gold elements or an acid waste solution containing gold elements.
[0017] Preferably, the acidic solution contains Pd 2+ , Pt 4+ , Ba 2+ , K + 、Na + , Ca 2+ 、Co 2+ , Fe 3+ Mg 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , Mn 2+ , Hg 2+ , Pb 2+ 、Al 3+ and Cd 2+ The concentration of each interfering ion in the solution can be at least 50 mg / L.
[0018] Preferably, when the acidic simulated liquid containing gold elements is a NaAuCl4 solution with a pH value of 1.0 to 10.0, the amount of Wurster-type covalent organic framework material used is 2 mg; the initial concentration of gold elements in the acidic simulated solution is 50 to 500 mg / L; the shaking mixing condition is shaking at 25°C for 24 hours; and the filtration is performed using a 0.22 μm filter head.
[0019] Preferably, it is characterized in that the acidic waste liquid containing gold elements is a leaching liquid of at least one of a circuit board, a CPU, and a wafer chip.
[0020] Preferably, when the acidic solution is a leaching solution obtained by mixing a circuit board and a CPU, the absorption rate of the gold element is 99.9%.
[0021] Another aspect of the present application also provides a method for preparing the Wurster type covalent organic framework material as claimed in claim 1, comprising the following steps:
[0022] Mixing the reaction raw materials and the reaction solvent and then ultrasonicating to obtain a mixture;
[0023] To the resulting mixture was added an aqueous solution of acetic acid, which was degassed by three freeze-pump-thaw cycles in a liquid nitrogen bath, and heated at a constant temperature to obtain a solid;
[0024] The solid obtained after Soxhlet extraction and drying is a Wurster type covalent organic framework material;
[0025] The reaction raw materials are at least two of the monomers A to C of the structural formula shown below;
[0026]
[0027] From the above monomer A~C structures, it can be seen that the raw material combination for the Schiff base reaction to form COF can be: monomer A+B, monomer B+C, monomer A+B+C;
[0028] Preferably, the reaction solvent is a mixture of o-dichlorobenzene and n-butanol in a volume ratio of 1:1, or a mixture of trimethylol and cyclohexane in a volume ratio of 1:1; the constant temperature heating is heating the reaction at 100-140° C. for 48-96 hours;
[0029] The concentration of the acetic acid aqueous solution used is 5-8 mol / L, and the acetic acid aqueous solution additive is 0.1-0.3 ml;
[0030] The washing solvents used in Soxhlet extraction were acetone, tetrahydrofuran and n-hexane, respectively;
[0031] The method also includes: after performing Soxhlet extraction on the obtained solid for 20 to 28 hours, vacuum drying at 60 to 80° C. is performed to obtain the Wurster type covalent organic framework material.
[0032] Preferably, when the reaction raw materials are phthalaldehyde substances and N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine, the molar ratio of phthalaldehyde substances and N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine is: 1:0.5;
[0033] When the reaction raw materials are monomer B, monomer A, and monomer C, the molar ratio of monomer B:monomer A+C is 1:2.
[0034] The beneficial effects of this application include:
[0035] 1) The Wurster-type covalent organic framework material, preparation method and application in gold adsorption provided in this application adopt a three-component mixed ligand strategy, with electron-rich Wurster-type monomers as building blocks, and successfully construct a series of novel three-component covalent organic frameworks with multi-level pore structures by adjusting the ratio of linear monomers and V-type monomers. By rationally regulating the ratio of isomers, this method achieves effective regulation of the original COF morphology and pore structure. The three-component Wurster-type covalent organic framework of the present invention exhibits excellent selectivity and high adsorption capacity in electronic waste and metallurgical wastewater, and has important practical value.
[0036] 2) The Wurster-type covalent organic framework material, preparation method and application thereof in gold adsorption provided in the present application have an adsorption rate of less than 5% for various impurity ions in acidic wastewater, but an adsorption rate of gold element as high as 99.9%. The gold element recovery rate in the mixed leaching solution of circuit boards and CPUs can reach 99.9%, and can be used for the adsorption and recovery of gold elements in various recycling materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The powder X-ray diffraction patterns of the covalent organic frameworks obtained in Examples 1 to 4 of the present application show the structural characteristics of the materials under different synthesis conditions. Figure 1 The black line in (a) is Tpa-2DCOF, the material obtained in Example 1; Figure 1 The blue line in (b) is TpaIda-2DCOF obtained in Example 2; Figure 1 The red line Ida-1DCOF in (b) is the substance obtained in Example 3; Figure 1 The green line in (b) is the IdaTpa-1DCOF obtained in Example 4; the two lines in the lower half of the figure are PXRD spectra simulated by the calculation software. Figure 1 (a) The experimental curve in the upper part matches well with the fitting curve of kgm-AA stacking. Figure 1(b) The experimental curve in the upper part matches well with the staggered stacking fitting curve. This shows that the addition of a small amount of isophthalaldehyde to terephthalaldehyde does not change the topological structure of the obtained covalent organic framework (i.e., the PXRD is almost the same); the addition of a small amount of terephthalaldehyde to isophthalaldehyde does not change the topological structure of the obtained covalent organic framework (i.e., the PXRD is almost the same).
[0038] Figure 2 The scanning electron microscope morphology images of the covalent organic framework materials obtained in Examples 1 to 4 of the present application show the morphological differences of different covalent organic framework materials. The differences in morphology indicate the effectiveness of the mixed monomer strategy in the synthesis. Figure 2 (a) is IdaTpa-1DCOF, the substance of Example 4; Figure 2 (b) Ida-1DCOF, the substance of Example 2; Figure 2 (c) Tpa-2DCOF, the material of Example 1; Figure 2 (d) is TpaIda-2DCOF, the material described in Example 3.
[0039] Figure 3 This is a scanning electron microscope morphology image of the material obtained in Example 3 of the present application after the material adsorbed the gold element, showing that gold nanoparticles are attached to the surface of the covalent organic framework, proving that the material has excellent adsorption properties; the red Au characters and similar shapes are gold nanoparticles, and the yellow circle is marked as TpaIda-2DCOF.
[0040] Figure 4 Schematic diagram of the raw material structure used in Examples 1-4 of the present application. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited in any way. Any changes or improvements made based on the teachings of the present invention fall within the protection scope of the present invention.
[0042] Example
[0043] Unless otherwise specified, the materials and instruments used in the following examples were obtained from commercial channels; the detection methods used were all existing methods unless otherwise specified.
[0044] Example 1: Preparation of 2D covalent organic framework
[0045] Terephthalaldehyde (structure: Figure 4 A, 13.4 mg, 0.10 mmol), N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine (structure Figure 41-(4-(4-(4-(4-chloro-2-yl)-1-yl)-2-nitropropene)-2-nitropropene-2-yl ...
[0046] The specific process of freeze-pump-thaw cycle degassing is: first place the glass tube in liquid nitrogen and freeze it for 1 minute, then turn on the vacuum pump to evacuate the air, turn off the vacuum after 5 minutes and flush nitrogen into the glass tube, then place the glass tube in water to completely melt all the solids. After the solids melt, repeat this process three times.
[0047] The mixture was heated at a constant temperature of 120°C in an oven for 3 days to obtain a mixture of a reddish brown precipitate and a solvent. After cooling to room temperature, the reddish brown solid was filtered and the solid precipitate was washed with tetrahydrofuran. After washing, the solid was placed in a tea bag and placed in a Soxhlet extractor. Acetone, tetrahydrofuran and n-hexane were used as solvents to continuously wash the solid in sequence for 24 hours. The solid was placed in a vacuum drying oven and evacuated to an internal pressure of 20mTorr, and dried at 80 degrees for 24 hours to obtain Tpa-2DCOF as a reddish brown powder (yield 92%). According to the network chemistry theory, the above-mentioned two symmetrical raw materials were used for reaction, and the constructed COF was a two-dimensional network structure.
[0048] The obtained Tpa-2DCOF material structure is shown below:
[0049]
[0050] Tpa-2DCOF is a schematic diagram of the structure of the material obtained in Example 1, which is a kgm topological structure with a hexagonal and triangular double pore structure.
[0051] Example 2: Preparation of TpaIda-2DCOF
[0052] The difference from Example 1 is that the raw material used is isophthalaldehyde (structure Figure 4 C, 2.7 mg, 0.02 mmol), terephthalaldehyde (structure Figure 4 A, 10.7 mg, 0.08 mmol) and N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine (structure Figure 4 B, 23.6 mg, 0.05 mmol) was synthesized and named TpaIda-2DCOF (yield 93%). The structure of the obtained TpaIda-2DCOF is shown below:
[0053]
[0054] TpaIda-2DCOF is a schematic diagram of the structure of the material obtained in Example 2, which is a deformed kgm topological structure with an irregular porous structure.
[0055] Example 3: Preparation of 1-dimensional covalent organic framework
[0056] The difference from Example 1 is that the raw materials used are: isophthalaldehyde (structure is Figure 4 C, 13.4 mg, 0.10 mmol), N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine (structure Figure 4 B, 23.6 mg, 0.05 mmol) was synthesized and named Ida-1DCOF (yield 95%). According to the network chemistry theory, the above two symmetrical raw materials were used for reaction, and the constructed COF was a one-dimensional ribbon structure. The obtained material structure is shown below:
[0057]
[0058] Ida-1DCOF is a schematic diagram of the material structure obtained in Example 3. The structure is a one-dimensional ribbon structure with a 4c-sql topological structure, a single-hole feature, and the ribbons are staggered and stacked.
[0059] Example 4: Preparation of IdaTpa-1DCOF
[0060] The difference from Example 1 is that the raw materials used are: terephthalaldehyde (structure Figure 4 A, 2.7 mg, 0.02 mmol), isophthalaldehyde (structure Figure 4 C, 10.7 mg, 0.08 mmol) and N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine (structure Figure 4 B, 23.6 mg, 0.05 mmol) and named IdaTpa-1DCOF (yield 90%).
[0061]
[0062] IdaTpa-1DCOF is a schematic diagram of the material structure obtained in Example 4, which is a deformed 4c-sql topological structure with an irregular porous structure.
[0063] Embodiment 5:
[0064] The difference from Example 1 is that the raw materials used are: the reaction solvent is a mixed solution of trimethylbenzene and hexacyclic epoxy in a volume ratio of 1:1. The constant temperature heating is heating reaction at 100°C for 48 hours. The concentration of the acetic acid aqueous solution used is 5 mol / L, and the acetic acid aqueous solution additive is 0.1 ml. After washing, Soxhlet extraction is performed for 20 hours, and then vacuum drying is performed at 60°C.
[0065] Embodiment 6:
[0066] The difference from Example 1 is that the raw materials used are: the reaction solvent is a mixed solution of trimethylbenzene and hexacyclic epoxy in a volume ratio of 1:1. The constant temperature heating is heating reaction at 140°C for 96 hours. The concentration of the acetic acid aqueous solution used is 8 mol / L, and the acetic acid aqueous solution additive is 0.3 ml. After washing, Soxhlet extraction is performed for 28 hours, and then vacuum drying is performed at 80°C.
[0067] By adjusting the ratio of terephthalaldehyde (monomer A) and isophthalaldehyde (monomer C), this method regulates the microscopic morphology of COF through a three-component one-pot method, changes the pore size distribution of COF, and realizes the controllable transformation of two-dimensional COF to one-dimensional COF. A multi-component COF with adjustable morphology, gradient dimension, high reduction activity and high selectivity was developed. Compared with the two-component COF, the three-component COF has a locally irregular topological structure and optimized electronic properties, and the two-dimensional / one-dimensional staggered structure significantly improves the mass transfer efficiency and reduction performance of the adsorbate.
[0068] According to the network chemistry theory, when the reaction raw materials have the symmetry of monomer A+B, the structure of the resulting material is a two-dimensional network structure, and when the reaction raw materials have the symmetry of monomer C+B, the resulting material is a one-dimensional strip structure. This difference comes from the fact that linear building units and high-symmetry building blocks are not restricted by steric hindrance when forming COFs, and are more easily transferred to the two-dimensional planar framework along the entire edge, while nonlinear linking blocks (such as 120°) usually lead to non-edge-source transmission of COFs topological structures when constructing COFs due to their inherent angle restrictions, thereby producing specific strip-shaped or linear frameworks; when the reaction raw materials are monomers B+A+C, when the amount of C is small, the structure of the resulting product is similar to that of the product obtained by A+B; when the amount of A is small, the structure of the resulting product is similar to that of the product obtained by B+C;
[0069] When the reaction raw materials are monomer A+B, the obtained structure is a stacked structure of nanosheets ( Figure 2 c); when B+C is used, it is a short nanorod structure ( Figure 2 b). When the reaction raw materials are monomers A+B+C, when the amount of C is small, the morphology of the material is a spherical or ellipsoidal structure; when the amount of A is small, the material has a soft ribbon-like structure. By adjusting the ratio of the reaction raw materials used, the morphology and pore structure of the product material can be effectively controlled.
[0070] Test case 1: Study on the recovery performance of gold by covalent organic framework
[0071] First, the purchased 1g / L gold standard stock solution (sodium chloroaurate solution) was diluted to 50-500mg / L, and then the covalent organic framework was adsorbed on gold in the simulated solution. The solution pH was controlled at 1.0-10.0, and the temperature was controlled at 15-35°. Each group of experiments was carried out three times, and the reported data were reported as the average value.
[0072] Test method: Take an aqueous solution of gold with different concentrations (20-500 mg / L), adjust it to a pH of 1.0-10.0 with NaOH and HCl, respectively, add 2 mg of the material powder obtained in each example, and oscillate at 25°C for 24 hours using a constant temperature oscillator. After filtering with a 0.22 μm filter head, the gold concentration in the filtrate is measured using an inductively coupled plasma emission spectrometer to calculate the adsorption capacity of the covalent organic framework for gold ions.
[0073] serial number Implementation of pH Adsorption capacity Simulated solution composition Example 1 2.0 2980mg / g <![CDATA[Containing only AuCl4 - > Example 2 2.0 2650mg / g <![CDATA[Containing only AuCl4 - > Example 3 2.0 3650mg / g <![CDATA[Containing only AuCl4 -- > Example 4 2.0 3210mg / g <![CDATA[Containing only AuCl4 - >
[0074] Test Example 2: Study on the Selective Performance of Covalent Organic Frameworks for Gold
[0075] The selective adsorption of covalent organic frameworks on various metal ions: Pd 2+ , Pt 4+ , Ba 2+ , K + 、Na + , Ca 2+ 、Co 2+ , Fe 3+ Mg 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , Mn 2+ , Hg 2+ , Pb 2+ 、Al 3+ and Cd 2+ Adsorption experiments were carried out in the presence of both.
[0076] First, prepare the solution containing the interfering metal ions as shown in the following table, Au 3+ The solution contains Au 3+ The concentration is 95 mg / L, the concentration of each interfering metal ion in the solution is 50 mg / L, and the pH of the obtained simulated solution is 2.0. After taking 4 portions of the simulated solution at 20 mL / portion, 2 mg of the material obtained in Examples 1 to 4 was added to each portion of the simulated solution, and a constant temperature oscillator was used to oscillate at 25° C. for 24 hours, and the mixed solution was filtered with a 0.22 μm filter head to obtain a filtrate, and then the content of the remaining metal ions in the filtrate was measured using an inductively coupled plasma emission spectrometer to calculate the adsorption amount and removal rate of the covalent organic framework for gold and other interfering ions.
[0077]
[0078] Test Example 3: Study on the gold recovery performance of covalent organic framework in actual leaching solution
[0079] The adsorption of gold by covalent organic frameworks in complex environments. The mixed leaching solution of circuit boards and CPUs was selected as the actual water body to investigate the gold recovery ability of covalent organic frameworks in complex environments.
[0080] First, buy discarded circuit boards and CPUs from recycling stations, cut them into small pieces, clean them and set them aside. Then immerse the pieces in aqua regia and stir until the gold on the surface is completely dissolved.
[0081] After the reaction, the residue and the solution are separated by filtration, and if necessary, the residue is subjected to secondary leaching to increase the leaching rate.
[0082] Then, the pH of the obtained experimental solution is adjusted to 1-2 to obtain a mixed leaching solution of a circuit board and a CPU.
[0083] Finally, the above solutions were divided into four parts, and the materials obtained in Examples 1 to 4 were added to the experimental solutions to recover gold. The reaction was carried out on a shaker for 24 hours, and the content of the remaining metal ions in the filtrate was measured by inductively coupled plasma emission spectrometry after filtration, and the adsorption amount and recovery rate of gold and interfering ions by the covalent organic framework were calculated.
[0084] serial number Other ion recoveries Gold recovery rate Load environment Example 1 <5% 99.9% Circuit board and CPU leachate Example 2 <5% 99.9% Circuit board and CPU leachate Example 3 <5% 99.9% Circuit board and CPU leachate Example 4 <5% 99.9% Circuit board and CPU leachate
[0085] Test Example 4
[0086] The difference from Test Example 3 is that the mixed leaching solution of the circuit board and CPU is replaced by the wafer chip leaching solution.
[0087] Test example
[0088] 1. XRD tests were performed on the materials obtained in Examples 1 to 4, and the results were as follows: Figure 1 shown.
[0089] Figure 1 The structural properties of the materials under different synthesis conditions are demonstrated. Figure 1 The black line in (a) is Tpa-2DCOF, the material obtained in Example 1; Figure 1 The blue line in (b) is TpaIda-2DCOF obtained in Example 2; Figure 1 The red line Ida-1DCOF in (b) is the substance obtained in Example 3; Figure 1 The green line in (b) is the IdaTpa-1DCOF obtained in Example 4; the two lines in the lower half of the figure are PXRD spectra simulated by the calculation software. Figure 1(a) The experimental curve in the upper part matches well with the fitting curve of kgm-AA stacking. Figure 1 (b) The experimental curve in the upper part matches well with the staggered stacking fitting curve. This shows that the addition of a small amount of isophthalaldehyde to terephthalaldehyde does not change the topological structure of the obtained covalent organic framework (i.e., the PXRD is almost the same); the addition of a small amount of terephthalaldehyde to isophthalaldehyde does not change the topological structure of the obtained covalent organic framework (i.e., the PXRD is almost the same).
[0090] 2. The materials obtained in Examples 1 to 4 were respectively tested by scanning electron microscope, and the results obtained are as follows: Figure 2 As shown, the morphological differences of different covalent organic framework materials are demonstrated, and the different morphologies indicate the effectiveness of the mixed monomer strategy in synthesis. Figure 2 (a) IdaTpa-1DCOF, the material of Example 4, has a soft ribbon-like structure and has a good adsorption effect on gold; Figure 2 (b) Ida-1DCOF is the material of Example 2, showing short nanorods. The material has many adsorption sites on the surface and can adsorb gold elements well. Figure 2 (c) Tpa-2DCOF, the material of Example 1, has a nanosheet stacking structure, has many adsorption sites on the surface of the material, and can better adsorb gold elements; Figure 2 (d) is TpaIda-2DCOF, the substance in Example 3, which has a spherical or ellipsoidal structure, has many adsorption sites on the surface of the material, and can adsorb gold elements well; comparing the morphologies of Tpa-2DCOF and TpaIda-2DCOF, it is found that they are not the same substance; comparing the morphologies of Ida-1DCOF and IdaTpa-1DCOF, it is found that they are not the same substance;
[0091] 3. The material obtained in Example 3 after the absorption of gold element was subjected to scanning electron microscopy, and the results were as follows: Figure 3 As shown by Figure 3 It can be seen that gold nanoparticles are attached to the surface of the covalent organic framework, proving that the material has excellent adsorption properties; the red Au characters and similar shapes are gold nanoparticles, and the yellow circle is marked as TpaIda-2DCOF.
[0092] In summary, the present invention successfully synthesized a variety of Wurster covalent organic frameworks, and systematically studied their adsorption properties through experimental measurement and adsorption system modeling. The results show that the three-component covalent organic framework described in the present invention has excellent adsorption performance for AuCl4-, and the adsorption capacity varies with the change of the covalent organic framework structure. In addition, the three-component covalent organic framework exhibits highly selective adsorption of AuCl4- in interfering ion solutions, and can efficiently reduce AuCl4- to Au(0). It is worth noting that the three-component covalent organic framework material described in the present invention has low raw material cost, simple synthesis method and significantly better adsorption capacity than traditional materials. Therefore, the three-component Wurster covalent organic framework can be used as a high-performance adsorbent for treating electronic waste leachate, and has broad application prospects.
[0093] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A Wurster type covalent organic framework material, characterized in that: The structural formula is any of the following:
2. Use of the Wurster type covalent organic framework material as claimed in claim 1 in gold adsorption, with a gold recovery rate of >99.9%.
3. A method for gold element adsorption recovery, characterized in that: include: In an acidic solution, the Wurster type covalent organic framework material as claimed in claim 1 is added, the mixture is shaken and mixed, and the mixture is filtered, and the gold element is adsorbed into the obtained solid; The acid solution is an acid simulation solution containing gold elements or an acid waste solution containing gold elements.
4. The gold element adsorption recovery method according to claim 3, characterized in that: Acidic solution containing Pd 2+ , Pt 4+ , Ba 2+ , K + 、Na + , Ca 2+ 、Co 2+ , Fe 3+ Mg 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , Mn 2+ , Hg 2+ , Pb 2+ 、Al 3+ and Cd 2+ At least one of .
5. The gold element adsorption recovery method according to claim 3, characterized in that: When the acidic simulated liquid containing gold element is a NaAuCl4 solution with a pH value of 1.0 to 10.0, the amount of Wurster-type covalent organic framework material used is 2 mg; the initial concentration of gold element in the acidic simulated solution is 50 to 500 mg / L; the shaking mixing condition is shaking at 25°C for 24 hours; and the filtration is performed using a 0.22 μm filter head.
6. The gold element adsorption recovery method according to claim 3, characterized in that: The acidic waste liquid containing gold elements is a leaching liquid of at least one of a circuit board, a CPU, and a wafer chip.
7. The gold element adsorption recovery method according to claim 6, characterized in that: When the acid solution is the leaching solution of the mixed circuit board and CPU, the recovery rate of gold element is 99.9%.
8. A method for preparing a Wurster type covalent organic framework material as claimed in claim 1, characterized in that: The following steps are involved: Mixing the reaction raw materials and the reaction solvent and then ultrasonicating to obtain a mixture; To the resulting mixture was added an aqueous solution of acetic acid, which was degassed by three freeze-pump-thaw cycles in a liquid nitrogen bath, and heated at a constant temperature to obtain a solid; The solid obtained after Soxhlet extraction and drying is a Wurster type covalent organic framework material; The reaction raw materials are at least two of the monomers A to C of the structural formula shown below; 9. The preparation method according to claim 8, characterized in that: The reaction solvent is a mixture of o-dichlorobenzene and n-butanol in a volume ratio of 1:1, or a mixture of trimethylol and hexacyclopentane in a volume ratio of 1:1; the constant temperature heating is heating the reaction at 100-140°C for 48-96h; The concentration of the acetic acid aqueous solution used is 5-8 mol / L, and the acetic acid aqueous solution additive is 0.1-0.3 ml; The washing solvents used in Soxhlet extraction were acetone, tetrahydrofuran and n-hexane, respectively; The method also includes: performing Soxhlet extraction on the obtained solid for 20 to 28 hours, and then vacuum drying at 60 to 80° C. to obtain the Wurster type covalent organic framework material.
10. The preparation method according to claim 8, characterized in that: When the reaction raw materials are phthalaldehyde substances and N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine, the molar ratio of phthalaldehyde substances and N,N,N',N'-tetrakis(p-aminophenyl)-p-phenylenediamine is 1:0.5; When the reaction raw materials are monomer A, monomer B, and monomer C, the molar ratio of monomer B:monomer A+C is 1:2.
Citation Information
Patent Citations
Crown ether covalent organic framework material, preparation method and application of crown ether covalent organic framework material in adsorbing and separating palladium
CN115246914A
Porous composite material as well as preparation method and application thereof
CN115646465A
Hydrochromic covalent organic framework film as well as preparation method and application thereof
CN114804652A
Preparation and application of covalent organic framework supported catalyst
CN116832861A
Preparation method and application of electrochromic covalent organic framework film
CN118581473A